Macroinvertebrate community patterns in relation to leaf‐associated periphyton under contrasting light and nutrient conditions in headwater streams. (2nd January 2020) - Eckert, Rebecca A.; Halvorson, Halvor M.; Kuehn, Kevin A.; Lamp, William O.
Abstract: Temperate headwater streams traditionally have been considered heterotrophic and brown food web dominated with little primary production. Recent work, however, suggests algae on leaves in these streams may play a greater role than previously thought through interactions with microbial decomposers like fungi. Algae also may be important for macroinvertebrates colonizing leaves in streams. Algae are a more nutritious food resource for shredders than fungi and bacteria and provide a food resource for non‐shredder macroinvertebrates. In a field experiment, we manipulated light in three low‐nutrient and three high‐nutrient streams using leaf bags filled with red maple leaves in winter and spring. After four weeks we measured algal and fungal biomass, leaf stoichiometry, and macroinvertebrate abundance and biomass associated with the leaf bags. We also identified the macroinvertebrate community and examined differences in functional feeding guilds and taxa under ambient‐ and shaded‐light treatments and low‐ and high‐nutrient concentrations in relation to measured leaf characteristics. Algal biomass on leaves was greatest in high‐nutrient streams and ambient‐light treatments in both seasons. Fungal biomass on leaves was greatest in high‐nutrient streams and showed a moderate marginally significant positive correlation with algae during the winter. Leaf C:N was negatively correlated to algae in winter and fungi in both seasons, while leaf N:P and C:P were negatively correlated to fungi in winter and algae in spring. Interactions between fungi and algae on leaves and the nutritional importance of each for macroinvertebrates likely change across seasons, potentially impacting macroinvertebrate community composition. Macroinvertebrate diversity did not differ, but biomass was significantly greater in shaded‐light treatments during spring. Abundance was highest in the high‐nutrient ambient‐light conditions in both seasons, corresponding to greatest algal biomass. Functional feeding guild biomass and abundance were related to different leaf characteristics by season and guild. Higher algal biomass was an important factor for colonization of certain macroinvertebrates (e.g., Ephemerella (Ephemeroptera: Ephemerellidae) and Stenonema (Ephemeroptera: Heptageniidae)), while others were more abundant under shaded treatments with lower algal biomass (e.g., Tipula (Diptera: Tipulidae)), indicating taxa‐specific responses. Leaf‐associated algae may be an important factor mediating macroinvertebrate communities associated with leaves in temperate headwater streams. Our results demonstrate that green and brown food webs intersect within leaf packs, and they cannot be easily disentangled. We therefore should consider both autochthonous and allochthonous resources within headwater streams when examining their communities or developing water management strategies.